IgE-mediated cow’s milk allergy and sensitization in children with moderate to severe atopic dermatitis in Egypt - Gadelrab, Heba; Galal, Ashraf; Eissa, Maged; Eldeeb, Marwa; Shoman, Walaa (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Atopic dermatitis (AD) is a chronic, relapsing inflammatory skin condition frequently associated with food allergies, particularly cow’s milk allergy (CMA). Understanding the prevalence of IgE-mediated CMA and its relationship with AD is critical for early diagnosis and management. This study aimed to determine the frequency of IgE-mediated cow’s milk allergy and sensitization among children with moderate to severe atopic dermatitis attending the Allergy Clinic at Alexandria University Children’s Hospital. Methods: A prospective cohort study was conducted on 83 children with moderate or severe AD. Detailed clinical histories, SCORAD scoring, and skin prick tests (SPT) using commercial milk extract were performed. IgE-mediated CMA was diagnosed based on positive SPT and immediate clinical reactions after milk ingestion. Results: Cow’s milk sensitization was detected in 30.1% of patients, while confirmed IgE-mediated CMA was found in 19.3%. All allergic children had infantile-onset AD, with a statistically significant association between early-onset eczema and milk allergy (P:<0.001). No significant correlations were found between CMA and type of early feeding or age of solid food introduction. A majority of allergic children (75%) were exclusively breastfed. Conclusions: IgE-mediated cow’s milk allergy is prevalent among children with moderate to severe AD in Egypt and is significantly associated with early-onset eczema. These findings highlight the need for targeted allergy screening in infants presenting with AD.